ANALISA PROFITABILITAS PT BPD JAWA BARAT DAN BANTEN TBK TAHUN 2020 - Muhammad Albi Ferdiansyah, (2021)
This writing aims to find out how the condition of profitability of Pt Bpd West Java and Banten Tbk in 2020. Profitability itself is a ratio calculation in the financial statements to see the company's performance in generating profits. The method in carrying out this analysis is to collect Pt Bpd West Java and Banten Tbk report data in 2020 in the form of a balance sheet and income statement, then sort out any accounts in the balance sheet and income statement that are used in the calculation of profitability. The formula for calculating profitability used is there six, namely Gross Profit Margin (GPM), Net Profit Margin (NPM), Net Interest Margin (NIM), Return on Assets (ROA), Return on Equity (ROE), and Operating Expenses to Operating Income (BOPO). after all the ratio formulas are calculated, then the figure is tested with a standard ratio based on BI circular letter No. 6/23/DPNP dated 31 May 2004 and the expert opinion of cashmere in the book Analysis of financial statements in 2008. The results of this analysis are that there are two ratios that show negative results are Gross Profit Margin (GPM) and Net Profit Margin (NPM), then positive results because performance continues to increase from month to month are obtained using three calculations, namely Net Interest Margin (NIM), Return on Assets (ROA), and Return on Equity (ROE), one ratio that always shows positive results throughout the year is the analysis of the ratio of Operating Expenses to Operating Income (BOPO)